Intervención de enfermería y su relación con la aplicación de la teoría de orem durante el embarazo. Subcentro de Salud Barreiro. Babahoyo, Los Ríos, octubre 2018-abril 2019 - Carriel Guerrero, Gisella Elizabeth (2019)
Introduction. Nursing interventions in the self-care of pregnant women are essential in nursing practice because they contribute to meet the demand for therapeutic self-care. General objective. To analyze the relationship between the nursing intervention and the application of the Orem Theory in pregnant women who are treated at the Barreiro Health Sub-Center, Babahoyo, Los Ríos province, from October 2018 to April 2019. Methodology. The modality of the research, according to the level of measurement and analysis of the information had a qualitative-quantitative approach, according to the level of the study was exploratory and descriptive, for the purpose it was applied and not experimental and according to the temporal dimension was transversal. Information gathering techniques were used as unscientific scientific observation, direct and survey; A questionnaire was applied as an instrument. The universe and the sample were 30 pregnant women respectively, sampling was intentional non-probabilistic. Results. Prevalence of age between 20 to 24 years (36, 6%), with secondary (63.3%), in free union (70%), housewives (70%), 86.6% with low socioeconomic status. Deficit of self-care for internal douching (100%), never perform physical exercise (50%), 40% do not consume legumes, 20% never attend prenatal check-ups, 86.6% receive self-care orientation, nursing recognizes needs of health in 93.2%, provide information on maternity and paternity (83.2%). Conclusions. The application of the Orem theory and the nursing interventions showed correspondence, expressed in the ability of pregnant women to act, which allowed identifying situations that guide care